DEVELOPING PODCAST OF ENGLISH SONG AS MEDIA FOR ELT LISTENING - Amirudin Latif (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2015)
Abstract:Listening is one of the fundamental language skills.Based on the pre survey research, many students at Senior High School were not interested in listening course.This research tried to develop podcast of English song (PES) as the media in order to help the teacher in the teaching of listening and make the students interested in listening course. The type of the reseacher is developmental research.The steps of this research are self evaluation, expert review and one-to-one, small group, and field test. The subjects of this research are the students of SMAN 03 Metro and SMK Muhammadiyah 03 Metro. The researcher collected the data by giving some questionnaires to the expert review and students to find out whether the media is applicable and suitable or not. The result showed that: first, most of the studentsfelt fun and enjoyable in the learning process of listening course. Second, PES media was applicable, the students were active, very enthusiastic, excited with PES media. Key Words: English song, Listening media, Podcast.